Pengaruh Content Marketing Terhadap Keputusan Pembelian Pengguna ShopeePay Pada Masyarakat Kabupaten Karawang - Agus Supriatna; Nuraidah Nuraidah; Tri Gustian Anugrah (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to analyze the effect of content marketing on purchasing decisions. The population in this study are ShopeePay users in Karawang Regency. The sampling technique used was snowball sampling. Data analysis technique using simple linear regression. The results of the study show that content marketing has an effect on purchasing decisions